The influence of AI-powered personalization on brand loyalty in the fashion industry - Bilro, R.G. (2025 Global Marketing Conference at Hong-Kong, 2025)
This study explores the impact of AI-driven personalization on brand loyalty in the fashion industry. It examines how emotional connection (EC) and self-brand connection (SBC) influence online brand consumer engagement (OBCE) through personalized direct marketing campaigns. Using a quantitative survey and regression analysis, the research aims to validate the model and provide insights into enhancing consumer loyalty. This study fills a gap by focusing on the relationship between AI-driven personalization and brand loyalty in direct marketing campaigns.